Echocardiographic assessment of pediatric semilunar valve disease. Issue 9 (31st March 2017) - Cantinotti, Massimiliano; Giordano, Raffaele; Emdin, Michele; Assanta, Nadia; Crocetti, Maura; Marotta, Marco; Iervasi, Giorgio; Lopez, Leo; Kutty, Shelby
Abstract : We reviewed echocardiography literature for the assessment and management of semilunar valve disease in children. A search was performed within the National Library of Medicine using the keywords aortic stenosis (AS), aortic regurgitation, pulmonary stenosis (PS), and pulmonary regurgitation in children. The search was further refined adding the keywords—pediatric, neonates, echocardiographic definition, classification, evaluation. Thirty‐eight studies were included. For stenotic lesions, there were sufficient consistencies between Doppler and invasive gradients (especially for PS), while other quantitative parameters used in adults showed significant limitations when applied to children. Heterogeneities remain in the range of Doppler measurements utilized to define mild vs moderate vs severe AS/PS, and to guide management. There is sufficient consensus regarding indications for interventions. In regurgitant lesions, there is weak evidence supporting the use of quantitative or semiquantitative parameters after correction for body surface area; clear indications for intervention are lacking. Because adult echocardiographic recommendations cannot be simply translated to the pediatric age, more specific pediatric guidelines and standards for the assessment of semilunar valve disease are needed.